1995
DOI: 10.1021/bi00040a025
|View full text |Cite
|
Sign up to set email alerts
|

The Tissue-Specific Nuclear Matrix Protein, NMP-2, Is a Member of the AML/PEBP2/Runt Domain Transcription Factor Family: Interactions with the Osteocalcin Gene Promoter

Abstract: The nuclear matrix protein, NMP-2, was originally identified as an osteoblast-specific DNA-binding complex localized exclusively to the nuclear matrix. NMP-2 was shown to recognize two binding sites, site A (nt-605 to -599) and site B (nt -441 to -435), in the rat bone-specific osteocalcin gene promoter. This study shows that the NMP-2 binding sites A and B as well as a third NMP-2 binding site (nt -135 to -130) constitute a consensus sequence, ATGCTGGT, and represent an AML-1 recognition motif. AML-1 is a mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
210
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 240 publications
(223 citation statements)
references
References 41 publications
12
210
0
1
Order By: Relevance
“…PEBP2/CBF␣ family members (also termed polyoma virus enhancer binding protein 2, or PEBP2␣; and acute myelogenous leukemia factors; Refs. 19 -21) were previously identified in nuclear extracts from differentiated osteoblasts and found to have a critical role in the expression of the osteoblast-related protein, osteocalcin (18,42,43). Our studies with the TGF-␤RI have now identified a new target for PEBP2/CBF␣ activity beyond the virus-infected or immunological tissues where their identity was first established (19).…”
Section: Fig 10mentioning
confidence: 60%
“…PEBP2/CBF␣ family members (also termed polyoma virus enhancer binding protein 2, or PEBP2␣; and acute myelogenous leukemia factors; Refs. 19 -21) were previously identified in nuclear extracts from differentiated osteoblasts and found to have a critical role in the expression of the osteoblast-related protein, osteocalcin (18,42,43). Our studies with the TGF-␤RI have now identified a new target for PEBP2/CBF␣ activity beyond the virus-infected or immunological tissues where their identity was first established (19).…”
Section: Fig 10mentioning
confidence: 60%
“…After signalinduced activation, these proteins interact with transcription factors and act on target genes (1)(2)(3)(4). A broad range of nuclear proteins including tissue-restricted transcription factors (e.g., Runx proteins), chromatin-remodeling complexes (e.g., SWI͞ SNF), components of basal transcription machinery (e.g., active form of RNA Pol II), and proteins involved in RNA processing (e.g., SC35) exhibit distinct subnuclear distributions (5)(6)(7)(8). The subnuclear organization of these regulatory complexes may determine their optimal functions.…”
Section: Ammalian Cells Respond To a Vast Array Of Extracellularmentioning
confidence: 99%
“…Overexpression of Runx2 and osterix in engineered MSCs may direct osteoblastic lineage differentiation and suppress other lineage differentiation (Merriman et al, 1995;Nakashima et al, 2002). Runx2-engineered MSCs directly enhance the repair of critical-sized calvarial defects when implanted solely (Zheng et al, 2004;Zhao et al, 2007) and form more bone when used in BTE (Zhao et al, 2005;Byers et al, 2006).…”
Section: Taz Sox9mentioning
confidence: 99%